Performance Hospital Service Against The Level Of Anxiety In Child - Erni Nuryanti; Suharto Suharto; Endang Nurnaningsih (Poltekkes Kemenkes Semarang, 2014)
Hospitalization in children is a crisis condition when children are sick and they need to be treated at hospital. Mostly, children who are hospitalized will experience anxiety. The services providd by nurses, doctor and laboratory personal affect the level of anxiety in children. The method used in this reseach is survey with the use of quationnaire as a data collection tool. This research involve some children who are hospitalized in dr R Soetijono and Permata Hospital in Blora as the samples of this research which were taken with a total sampling method. Data analyzed with the Sperman Rho method. The result of the research study in dr R Soetijono Blora hospital shows is connection between the performance nurses (p=0,006) and the performance doctor (p=0,008). There is no connection beetween the level of anxiety and the performance of laboratory personnel (p=0,431). The study in Permata Hospital Blora shows that there is connection between performance nurses (0,391) and performance doctor (0,019). Moreovere, there is no connection beetween the level of anxiety and the performance of laboratory personnel (p=0,258).